Origins, belonging, and expectations: assessing resource compensation and reinforcement in academic educational trajectories - Burger, Kaspar; Brack, Nathan (Social forces, 2025)
Research has shown that socioeconomic and psychological resources may influence educational trajectories. There are still unanswered questions, however, about the unique roles of these resources and the interplay between them. We consider two such questions: First, how do major psychological resources—a sense of school belonging and optimistic future expectations—predict educational trajectories when controlling for the effect of socioeconomic resources? And, second, do these psychological resources compensate for lacking socioeconomic resources or do they reinforce the influence of socioeconomic resources on educational trajectories? We used data from a 15-year-long Swiss panel study (N = 1989) and investigated educational trajectories concerning individuals’ transitions from lower-secondary to academic upper-secondary education, and from there to university. Findings indicated that both socioeconomic and psychological resources were significantly associated with individuals’ probability of transitioning to academic upper-secondary education. We also uncovered some evidence of resource compensation between socioeconomic resources and future expectations, suggesting that optimistic expectations may buffer the adverse effect of scarce socioeconomic resources on educational attainment. Furthermore, we found that both the sense of school belonging and future expectations were significantly associated with individuals’ probability of transitioning to university. Overall, we conclude that psychological resources play a critical role in academically oriented educational trajectories and that they may partly compensate for the effects of limited socioeconomic resources on these trajectories.